Surgical correction of fistulas in patients with cervical cancer after radiation therapy - M. N. Saryev; M. I. Nechushkin; R. K. Valiev; M. B. Nurberdyev; V. A. Aliev; E. A. Tizilova (Тазовая хирургия и онкология, 2022)
The aim of this study was to analyze currently available information on the risks of fistulas in patients with cervical cancer after radiation therapy and possible treatment options.This review includes data from Russian and foreign articles devoted to this problem. It covers the frequency of fistulas of after radiation therapy in cervical cancer patients, as well as some treatment methods.Attempts to change the approaches to radiation therapy for advanced cervical cancer were unsuccessful; therefore, patients with cervical cancer will be at high risk of developing fistulas in the next few years. Different treatments for fistulas demonstrate contradictory results and dictate the need for a tailored-approach in such cases. The development of new surgical methods for the correction of vesicovaginal and rectovaginal fistulas is still highly relevant.